Development of Potato Chip Cluster Supply Chain Institutional Model with The Integration of ISM (Interpretive Structural Modeling) and ANP (Analytic Network Process) - Prabaningtias, Nadya; Mustaniroh, Siti Asmaul; Dania, Wike Agustin Prima (agriTECH, 2024)
Increasing the productivity of potato chip in Micro, Small, and Medium Enterprises (MSMEs) through the institutional model is significantly strengthening the economy of Batu City, especially as a tourist destination city. The institutional model ensures the smooth operation of supply chain activities due to the interactions between the actors, facilitating coordination, information sharing, and integration from upstream to downstream. This model can be used to improve the performance. To improve the performance, supply chain of potato chip MSMEs cluster faces several challenges including a limited supply of raw materials and finished products, price fluctuations, non-optimal drying processes, and inconsistent quality. Therefore, the study aimed to conduct a holistic evaluation and improvement method on the interconnected constraints to enhance supply chain’s performance. The integration of Interpretive Structural Modelling (ISM) and Analytic Network Process (ANP) methods was applied to observe interactions between key elements in development of supply chain institutional potentials and to prioritize development strategies. The results showed that the key elements that influenced development of the organizations related to labor capability, diversity of raw material quality, the potential for collaboration relationships, minimizing the risk of drying during the rainy season, and participation of various actors. Based on the largest WANP weight value (0.230), the primary strategy for supply chain development in the SME cluster was the implementation of digital-based marketing. Furthermore, improving the institutional performance model of potato chip MSMEs cluster supply chain included the participation of internal and external quality assurance organizations in the product quality audit process. Ensuring product quality consistency through these audits would support digital-based marketing and help mitigate issues related to product quality and supply consistency.